Intergenerational Economic Mobility and Assortative Mating - John Ermisch; Marco Francesconi; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
We use data from the German Socio-Economic Panel and the British Household Panel Survey to estimate the extent of intergenerational economic mobility in a framework that highlights the role played by assortative mating. We find that assortative mating plays an important role. On average about 40-50 percent of the covariance between parents? and own permanent family income can be attributed to the person to whom one is married. This effect is driven by strong spouse correlations in human capital.
Keywords: I20; D64; J12; D31; 330; Intergenerational links; marriage market; assortative mating; occupational prestige